The geographies of enlightenment Edinburgh - Dodds, Philip Andrew (Studies in the eighteenth century, 2022)
This innovative book explores how the making of Edinburgh as an influential Enlightenment capital depended on a series of spatial processes that extended across urban, regional, national and global scales.